TOKOH WAYANG SEMAR SEBAGAI BUDAYA LOKAL INDONESIA DALAM RANGKA MEMPERKAYA IMAJINASI DAN SUMBER KREATIVITAS DEKAVE - Endro Tri Susdarwono (Universitas Negeri makassar, 2020)
The purpose of this study is to discuss the Semar puppet characters who are Indonesian local culture as a wealth of imagination and a source of creativity in the creation of visual communication design works. This research is a qualitative research, the type of research uses a comprehensive analytical study and analytical normative approach. Indonesian local culture needs to be embraced into a wealth of imagination and a source of creativity for the process of creating advertising design works. By following the prevailing customs, upholding morality, and prioritizing local cultural wisdom to be later appointed as inspiration, source of ideas and ideas, as well as software to communicate various commercial, social, or moral messages to the target audience, existence A visual communication design work will accentuate people's lives, in the end it is expected to be able to enlighten the thoughts and feelings of human beings who live and fill their lives according to their respective talents. The mysterious Semar wayang figure is also part of the religious mythological figure loved by the Javanese people in particular. Therefore, Semar is considered to have high value and value in wayang as part of Javanese life. So, of course the character Semar will be interesting to study more carefully and more deeply in terms of philosophy in an effort to unravel the mystery that surrounds him.